2020
DOI: 10.1016/j.ypmed.2019.105945
|View full text |Cite
|
Sign up to set email alerts
|

Playground features and physical activity in U.S. neighborhood parks

Abstract: All people need to engage in routine physical activity and children require it daily. Playgrounds are settings designed for children to be physically active, yet there has been little research assessing which play elements and structures are associated with more moderate-to-vigorous physical activity (MVPA) among both youth and adults. We conducted a national study of neighborhood parks with the goal of identifying factors that promote more MVPA. We selected a nationally representative sample of 162 parks betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 26 publications
4
41
0
Order By: Relevance
“…In the analysis, we exclude the public bus stop because all parks had this facility, and created a dichotomous variable called "availability of mass rapid transit" with the possible responses of yes or no. The population density was found to be associated with a higher amount of park-based physical activity in the park in previous studies [25,31,36]. We collected the district population density and park size from the BMA district office and incorporated it into the SOPARC responses for each park.…”
Section: Data Collectionmentioning
confidence: 99%
“…In the analysis, we exclude the public bus stop because all parks had this facility, and created a dichotomous variable called "availability of mass rapid transit" with the possible responses of yes or no. The population density was found to be associated with a higher amount of park-based physical activity in the park in previous studies [25,31,36]. We collected the district population density and park size from the BMA district office and incorporated it into the SOPARC responses for each park.…”
Section: Data Collectionmentioning
confidence: 99%
“…Yet this nding was reversed when examining the high-green park independently, which may be related to children's preference for a playground characterized by sparse canopy cover (i.e., 53.8% of all children observed), and their unwillingness to travel to large trees on the park's periphery during high heat index. Our nding that no children interacted with gardens or used nature trails may be due to these features being located far from play elements (e.g., slides, ladders, and swings), which have been shown to be associated with more users and more moderate-to-vigorous physical activity (56). In addition, installation of green features in a park may not induce the use of these spaces: researchers have found that living near sidewalk improvements was not associated with accelerometer-derived physical activity (57).…”
Section: Methodology For Climate and Health Solutionsmentioning
confidence: 90%
“…The annual economic cost of physical inactivity has been estimated as $53.8 billion, about 60% of which is borne by the public sector and 25% by households [24]. Strategies to address this preventable disease burden have included research to map limitations to engaging in physical activities across age groups and investments in infrastructure to increase physical activity at the population level [25][26][27][28][29][30][31]. Our goal with the present study was to contribute to the national evidence base of best practices for incentivizing physical activity in urban populations that are experiencing disproportional burden of chronic diseases, with emphasis on public recreational parks.…”
Section: Discussionmentioning
confidence: 99%